Mediasi dalam Al-Qur’an: Kajian Terhadap Ayat-Ayat Penyelesaian Sengketa Keluarga dan Dampaknya terhadap Pendidikan Anak - Romi, Muhammad; Khasanah, Niswatul; Ismail, Hidayatullah (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This study aims to examine the concept of mediation in the Qur'an as a solution to family dispute resolution and its impact on children's education. The method used in this research is qualitative with a literature study approach, which analyzes the verses of the Qur'an, tafsir, and related literature regarding mediation and child education in the family context. The results of the discussion show that the Qur'an strongly recommends mediation as the main step in resolving family conflicts, both in household problems and divorce, with the main objective of creating harmony and repairing relationships. The Qur'an also emphasizes the importance of the sincere intentions of the disputing parties, as the success of mediation depends largely on their sincerity. In addition, in the context of family conflict, children's education is an important aspect that should not be ignored. Islam emphasizes that children's education is a mandate that must be maintained, even in conditions of conflict. In conclusion, mediation based on the teachings of the Qur'an not only serves to resolve conflicts, but also safeguards the integrity and future of children, so as to create a generation that is moral, intelligent, and mentally strong even though it comes from a family that has experienced division.